2013
DOI: 10.1007/s12010-013-0188-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Oxidase/Cellulose–Carbon Nanotube Composite Paper as a Biocompatible Bioelectrode for Biofuel Cells

Abstract: Biofuel cells are devices for generating electrical energy directly from chemical energy of renewable biomass using biocatalysts such as enzymes. Efficient electrical communication between redox enzymes and electrodes is essential for enzymatic biofuel cells. Carbon nanotubes (CNTs) have been recognized as ideal electrode materials because of their high electrical conductivity, large surface area, and inertness. Electrodes consisting entirely of CNTs, which are known as CNT paper, have high surface areas but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Processing is a major challenge that is solved through the use of additives such as starch and clays [2] or surface treatment methods [3]. Several research groups have developed new, valuable products from recycled cellulose; such products include composite electrodes [4], bio-oil [5] and carbon dots [6].…”
Section: Introductionmentioning
confidence: 99%
“…Processing is a major challenge that is solved through the use of additives such as starch and clays [2] or surface treatment methods [3]. Several research groups have developed new, valuable products from recycled cellulose; such products include composite electrodes [4], bio-oil [5] and carbon dots [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Young's modulus of the composites tuned to reach 90 MPa with conductivity about 2.3 × 10 −4 to 2.2 × 10 −2 S cm −1 (Loos and Manas-Zloczower 2013). In consequence, composite materials consisting of CNTs combined with cellulose paper have developed, and found that the composite is able of shielding electromagnetic interference over the examined range of 15-40 GHz, mainly in the range of 30-40 GHz, with absorption as the critical shielding mechanism Won et al 2013). It is also found in other studies that both normal flexible paper and conducting CNTs demonstrated in the composite systems with a controllable volume resistivity within a range of 1.35-540 Ohm cm (Tanaka et al 2013).…”
Section: Cnts: In Cellulose Polymeric Compositesmentioning
confidence: 99%
“…There is a growing interest in paper recycling, because cellulosic products have been widely used and recycled in many industrial fields. Due to economic and environmental benefits, paper recycling rates have increased by nearly 20% within the last few decades. However, down-graded waste papers, which have been recycled several times, might not be recyclable due to fiber damage and decreased cellulose molecular weight during the process. A number of research groups have endeavored to convert lower quality waste paper into valuable products. In this regard, waste papers typically containing 90–99% cellulose derivatives can be worthy candidates for recycled, value-added product production.…”
Section: Introductionmentioning
confidence: 99%